Lattice distortion effects on the magneto-structural phase transition of MnAs. - SANVITO, STEFANO; RUNGGER, IVAN (My University, 2005)
We present a systematic experimental and theoretical study of the first-order phase transition of epitaxially grown MnAs thin films under biaxial tensile stress. Our results give direct information on the dependence of the phase-transition temperature of MnAs films on the lattice parameters. We demonstrate that an increase of the lattice constant in the hexagonal plane raises the phase-transition temperature (Tp), while an increase of the perpendicular lattice constant lowers Tp. The results of calculations based on density functional theory are in good agreement with the experimental ones. Our findings open exciting prospects for magneto-mechanical devices, where the critical temperature for ferromagnetism can be engineered by external stress.
PUBLISHED
PMID: 16196819
Keywords: biaxial tensile stress; biaxial tensile stress